The Furnas‐Mustardé Combination Technique for the Treatment of the Prominent Pinna: Our 17‐Year Experience. (2nd September 2014) - Deleito, Javier M.; Talwar, Rishi; Garcia‐Purriños, Francisco; Guillen, Alberto; Delvasto, Lorena; Barrios, Andres
Abstract : Objectives: Report a method using a combination of the Furnas and the Mustardé techniques for the treatment of prominent pinna. Methods: All the patients who underwent otoplasty under the supervision of a single surgeon between 1996 to 2013 were included. Surgical technique and complications were analyzed. Major complications were defined as those requiring revision surgery. Mustardé sutures were used to recreate the antihelix and correct upper/middle thirds of the pinna. In the conchal region, both conchal resection and the Furnas conchal‐mastoid sutures were frequently used. Prospective outcome measures included overall benefit and patient satisfaction. Results: A total of 130 patients with protruding ears were operated upon (126 bilateral, 4 unilateral). Therefore, there were 256 primary interventions. Fifteen required a pure Mustardé technique and 4 underwent a pure Furnas technique. Hence, the combined technique was applied to 237 ears. Mean follow‐up was 5 years (6 months‐17 years). Only 9 (3.5%) required revision surgery owing to unsatisfactory results and 1 (0.04%) due to bleeding. Minor complications included suture extrusion in 35 ears (13.6%), some up to 5 years postop, and 2 patients (0.07%) developed a retroauricular keloid (treated successfully with intralesional triamcinolone). Overall benefit perceived by the patients was reported as good in 77% and satisfactory in 18%. Conclusions: We present a technique that combines 2 previously well described techniques, using both cartilage resection in addition to permanent sutures. We believe that the good aesthetic results and acceptable number of complications make this technique an appropriate treatment option for patients with prominent ears.